ANALYSIS OF FACTOR FACTORS AFFECTING THE APPLICATION OF FINANCIAL ACCOUNTING STANDARDS OF ENTITIES WITHOUT PUBLIC ACCOUNTABILITY ON SMALL AND MEDIUM MICRO ENTERPRISES IN THE SURAKARTA CITY - Faridz Kurniawan; Setyani Sri Haryanti; Yuniatin Trisnawati DKW (ADVANCE, 2018)
This study aims to analyze factors that influence the application of SAK ETAP to SMEs in Surakarta City and obtain empirical evidence of the influence of Information and Socialization, Background of Education and Old Business on the Application of SAK ETAP on MSMEs registered in DINKOPUKM. Sample selection is done by using purposive sampling method with predetermined criteria. The result of the research shows that the variable of Information and Socialization give significant influence to the application of SAK ETAP because the regression coefficient value is 0.223 and the significance value is 0,015. Educational Background influence significantly to EAP Application of SAK is shown by regression coefficient value of 0.176 and significance value of 0.043. Length of Business significantly influence to Application of SAK ETAP is shown with regression coefficient value equal to 0,205 and significance value equal to 0,008. Keywords : Application of SAK ETAP, Background of Education, Length of Business and. Provision of Information and Socialization